2007
DOI: 10.1007/s11111-007-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring environmental perceptions, behaviors and awareness: water and water pollution in South Africa

Abstract: Understanding the relationships among perceptions, behaviors and awareness of environmental initiatives is important for both policy makers and social scientists. There is, however, limited consensus among scholars as to the reasons for differences and similarities among ethnic and socio-economic groups in their environmentally related attitudes and behaviors. South Africa, which has established a constitutional right to a safe environment, together with the presence of parallel first and third world populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 15 publications
1
57
0
2
Order By: Relevance
“…The relationships between perceptions, behaviours and awareness of environmental challenges have been explored in the South African context by Anderson et al (2007) and more recently by Wright et al (2012). They found that a relatively small percentage of people in South Africa treat their drinking water or perceive water pollution (and quality) as a serious concern, and that perceptions of drinking water safety have remained fairly stable from 2002 to 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between perceptions, behaviours and awareness of environmental challenges have been explored in the South African context by Anderson et al (2007) and more recently by Wright et al (2012). They found that a relatively small percentage of people in South Africa treat their drinking water or perceive water pollution (and quality) as a serious concern, and that perceptions of drinking water safety have remained fairly stable from 2002 to 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very little research has been conducted on the specific water-related beliefs and behaviours of African residents living in the NWP of South Africa, especially in impoverished communities where access to water might be problematic. Not only is the nature 433 and extent of residents' water use likely to be significantly influenced by these beliefs (Russel and Fielding, 2010), but attitudes related to water have been found to vary between African and other ethnic groups in South Africa (Anderson et al, 2007). The lack of research on this population group renders it difficult to plan and develop effective policies and interventions aimed at regulating people's interactions with water in order to meet their water-related needs, whilst simultaneously ensuring their safety and sustainable and optimal use of this scarce resource.…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers suggest concern for the environment is more likely in developed countries, where populations have a higher socio-economic status, other research suggests that environmental concern is equally prevalent in developing societies (Anderson, Romani, Phillips, Wentzel, Tlabela, 2007;Dunlap et al, 1993;Inglehart, 1995;Van Liere & Dunlap, 1980). Teasing out the influence of culture from socio-economic factors remains a highly relevant topic of research (Anderson, Wentzel, Romani, & Phillips, 2010).…”
Section: Cultural Variables and Environmental Attitudesmentioning
confidence: 99%
“…Sociodemographic variables were found to be important in understanding difference in energy consumption and emissions, suggesting that controlling for lifestyles and other determinants, emissions are increasing with income and decreasing with education (Baiocchi et al 2010). Despite these pro-environmental behaviors and lower consumption levels than in the more socioeconomically advantaged groups, there is also evidence of lower environmental awareness and noneconomically motivated environmental behavior in such groups (Anderson et al 2007). However, review of studies of regional differences and sociodemographic determinants of environmental concern demonstrate that research findings on such differences and determinants are inconsistent and occasionally contradictory due to lack of consensus on instrument to measure environmental attitudes (for a literature review, see Vining et al 1992 andGuagnano andMarkee 1995).…”
Section: Introductionmentioning
confidence: 99%